(untitled) (Research, Society and Development, 2020)
In the study, the Quality Index Method (MIQ) adapted for the entire Pangasius bocourti stored on ice for 25 days was applied, the freshness was evaluated and its shelf life and acceptable human consumption was estimated, using 80 specimens caught in a fish farm. located in the municipality of Bom Jardim - MA. Sensory analyzes of quality attributes were applied by five trained judges, in 10 copies/ ay. The scores were tabulated, estimating the mean and standard deviations for each of the five judges, for each attribute and sub-attribute obtained. The microbiological analyzes used eight specimens consisting of the use of the first specimen/day on each day of sensory analysis. The MIQ Protocol provided 0 - 33 demerit points, with six attributes and 15 quality sub-attributes. In the microbiological analyzes it was verified that the samples were within the standard established by Brazilian legislation even after 25 days of storage. It was concluded that the P. bocourti Quality Index Method was effective to assess the freshness and estimate the species’ useful life. The whole P. bocourti stored on ice remained with its sensory indexes suitable for human consumption assessed by MIQ for up to 12 days.